2011
DOI: 10.4141/cjps10185
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen remobilization and post-anthesis nitrogen uptake in relation to elevated grain protein concentration in durum wheat

Abstract: 2011. Nitrogen remobilization and post-anthesis nitrogen uptake in relation to elevated grain protein concentration in durum wheat. Can. J. Plant Sci. 91: 273Á282. Grain protein concentration is an important end-use suitability factor in durum wheat [Triticum turgidum L. ssp. durum (Desf.)Husn.] through its effect on cooking quality. Genetic differences in grain protein concentration are exploited in Canadian durum breeding programs, but the physiological basis of these differences remains unknown. Eighteen du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
2
12
0
2
Order By: Relevance
“…The genotype by environment interaction (G×E) was significant for all traits, except for harvest index (HI). These results are similar to those reported by Barraclough et al (2010), Haile et al (2012) and Suprayogi et al (2011). The coefficients of variation ranged from 2.0 to 7.4%, indicating high experimental precision.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The genotype by environment interaction (G×E) was significant for all traits, except for harvest index (HI). These results are similar to those reported by Barraclough et al (2010), Haile et al (2012) and Suprayogi et al (2011). The coefficients of variation ranged from 2.0 to 7.4%, indicating high experimental precision.…”
Section: Resultssupporting
confidence: 90%
“…In the present study, the NHI ranged from 0.71 to 0.84 (Figure 5a). It was characterized as existing low amplitude variation in Brazilian wheat cultivars compared to the results obtained by Barraclough et al (2010) and Suprayogi et al (2011) (Figure 5a). The NHI was positively correlated with GPC K (0.49*) only in Coxilha (Figure 6f ), agreeing partially with the results reported by Haile et al (2012), who found correlations between NHI and NUtEg (0.76) and GPC N (0.42 ).…”
Section: Resultsmentioning
confidence: 65%
“…Em nível fisiológico, a formação de proteínas, importantes no processo de germinação das sementes, envolve mecanismos de absorção de nitrogênio pelas raízes, acúmulo nos órgãos vegetativos e posterior remobilização para os grãos para a formação e configuração proteica (TRIBOÏ et al 2003). Este nitrogênio remobilizado é responsável por cerca de 80% do conteúdo total do nutriente no grão (SUPRAYOGI et al 2011 e aproveitamento deste nutriente. Pesquisas avaliando o efeito do parcelamento de nitrogênio durante a fase de panícula em arroz em consórcio com trigo revelaram que a aplicação antecipada de nitrogênio, reduz significativamente as perdas deste nutriente, assegurando uma alta taxa de absorção (XU et al 2015).…”
Section: Averages For Interaction Between Cultivars (Tbio Mestre Tbiunclassified
“…Nitrogen is a substance that plays an essential role in wheat crops due to stimulating tiller emergence and for actuating in the determination of the amount of grains per spike and the grain weight, which are yield primary components of crops (NARDINO et al 2013). Nitrogen remobilization from the plant vegetative structure to the grains is approximately 80% of the total nutrient content in the grains, while the remainder is provided by post-anthesis absorption (SUPRAYOGI et al 2011). The importance of a good availability of nitrogen in later stages such as in ear development is also because the ear spikelets are farthest from the base and have shorter nutrient accumulation periods, which may compromise the density thereof (ANDERSSON et al 2004).…”
Section: Introductionmentioning
confidence: 99%